2002
DOI: 10.1097/00007632-200201150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Functional and Radiologic Outcomes After Harrington Instrumentation and Spondylodesis in Adolescent Idiopathic Scoliosis

Abstract: In patients with adolescent idiopathic scoliosis who undergo surgery with Harrington instrumentation, the overall long-term clinical outcome does not correlate with the radiologic outcome. However, a significant inverse correlation was found between the magnitude of the primary thoracic curve at follow-up assessment and the scores for questions on cosmetic matters in the Scoliosis Research Society questionnaire. Spine mobility is diminished as a result of spondylodesis, but the patients perform, on the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
2
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 17 publications
2
60
2
8
Order By: Relevance
“…Whereas the studies of Danielsson et al [4] with a follow-up of 23 years and a significantly reduced quality of life compared with age matched individuals, the good results of our study and others [7][8][9]13] may be related to the shorter follow-up and the smaller study group. Padua [14] for example, could only locate 38% of patients but with a follow-up assessment of 37.5 years.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Whereas the studies of Danielsson et al [4] with a follow-up of 23 years and a significantly reduced quality of life compared with age matched individuals, the good results of our study and others [7][8][9]13] may be related to the shorter follow-up and the smaller study group. Padua [14] for example, could only locate 38% of patients but with a follow-up assessment of 37.5 years.…”
Section: Discussioncontrasting
confidence: 85%
“…However, such information has proved to correlate only weakly with outcomes that are more relevant to patients. Until recently, only a few long-term outcome studies have used standardized and validated patient-oriented tools to evaluate surgically treated patients with idiopathic scoliosis [1,3,4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Williers et al reported 40% final correction rate in a 10.8 years follow-up study [47]. Helenius et al reported relatively lower correction rates with Harrington rod system when compared with the C-D instrumentation [24]. Lespien stated that in 2 years following the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the long-term results in the literature are with the Harrington rod system [23,24,32,47]. Williers et al reported 40% final correction rate in a 10.8 years follow-up study [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation